Functionally public accountability, management control systems and organizational culture to increase organizational performances / David Pangaribuan Bhayangkara - Bhayangkara, David Pangaribuan (UiTM Cawangan Johor, 2023)
This study aims to examine the effect of public accountability, management control systems and culture organization to organizational performance. The type of research is descriptive quantitative using multiple linear regression. While, data collection uses questionnaires and purposive sampling with 60 respondents. As for the research results: Public accountability has a positive effect on organizational performance. Management control system has a positive effect on organizational performance. Organizational culture moderates relationship between public accountability and organizational performance and Organizational culture moderates relationship between management control systems and organizational performance. Public accountability, management control system and organizational culture play important roles in improving organizational performance. Keywords: Organizational Performance, Public Accountability, Management Control System, Organizational Culture